Analisis konsep ontologi pada filsafat pendidikan Islam, persepektif essensialisme, perennialisme, dan rekonstruksionisme - Ummi Sa'adah; Najwa Zuhrotul Auliya (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
Ontology in Islamic philosophy of education is a branch of knowledge that examines the nature of existence, both material and spiritual. This study aims to analyze the concept of ontology from the perspectives of essentialism, perennialism, and reconstructionism. The method used is a literature review, involving the collection of data from various relevant articles, journals, and books. The results of the study indicate that essentialism views education as an effort to preserve cultural and historical heritage through the reinforcement of time-tested foundational knowledge. Perennialism emphasizes the importance of logical and rational principles as truths that are eternal and universal, and thus not easily shaken by the changing times. Reconstructionism views reality as dynamic and all-encompassing, necessitating its reconstruction to achieve a better social order. In conclusion, these three schools of thought complement one another in building a holistic Islamic education, in which essentialism serves as the foundation of values, perennialism as the framework of divine truth, and reconstructionism as the driving force behind social innovation ensuring that education not only transfers knowledge but also shapes the whole person.